Treatment of endovenous heat-induced thrombosis (EHIT) with rivaroxaban (Xarelto®) - Werth, S.; Halbritter, K.; Mahlmann, A.; Weiss, N. (Phlebologie, 2015)
Introduction: Endovenous heat-induced thrombosis (EHIT) is a known complication after endovenous ablation of the superficial varicose veins (incidence rate 0–6 % (varies by definition and diagnostic algorithm). However, only expert suggestions for indication, duration and dosing of treatment drugs exist. The most common recommendation is low-molecular weight heparin in half-therapeutic dosage for EHIT class 2 and therapeutic dosage for patients with EHIT class 3 or 4. Rivaroxaban is an attractive option in the treatment of venous thromboembolic diseases due to the simplification of treatment.Case report: After successful ablation of the great saphenous vein (GSV) in a patient with complete insufficiency (Hach III) combined with sclerotherapy of superificial varicose veins of the calf the patient got a prophylactic anticoagulation with low-molecular weight heparin (LMWH) and compressions stockings grade II. Nevertheless we saw in the control-compression ultrasound after 7 days an asymptomatic EHIT class 1. Due the progression to EHIT class 3 after another seven days under watchful waiting we treated the patient with Rivaroxaban for 14 days. After the treatment we saw a complete resolution of the clot. Anticoagulant treatment and compression stockings (for three weeks after EVLT) were discontinued.Einleitung: Die endovenös hitze-induzierte Thrombose (EHIT) ist eine bekannte Komplikation nach endovenöser Ablation der Varikosis mit einem geschätzten Auftreten zwischen 0–6 % (Variation je nach Definition und Diagnosealgorithmus). Über die Behandlungsindikation, -dauer und Art der Behandlung bestehen bisher nur Expertenmeinungen, jedoch keine Leitlinienempfehlungen. Meist wird ab einer EHIT-Klasse 2 eine zumindest halbtherapeutische Gabe von niedermolekularem Heparin (NMH) empfohlen, ab einer EHITKlasse 3 und 4 auch in therapeutischer Dosierung. Rivaroxaban (Xarelto®) hat sich in der Therapie der venösen Thromboembolien (VTE) etabliert und die Behandlung deutlich simplifiziert.Fallbericht: Nach einer erfolgreichen endovenösen Laserablation der Vena saphena magna (VSM) bei kompletter Insuffizienz (Hach III) sowie in gleicher Sitzung durchgeführter Sklerotherapie von Seitastvarizen am Unterschenkel erhielt der Patient eine prophylaktische Antikoagulation mit niedermolekularem Heparin (NMH) und eine Kompressionstherapie mittles Oberschenkelstrumpf der Kompressionsklasse II, Trotzdem wurde in der Kompressionssonographie nach 7 Tagen eine asymptomatische EHIT Klasse 1 in der VSM diagnostiziert. Bei progredientem Be-fund in der Verlaufskontrolle nach einer Woche (watchful waiting) erhielt der Patient für 14 Tage Rivaroxaban. Abschließend zeigte sich eine komplette Rekanalisation der EHIT. Die Antikoagulation und Kompressionstherapie (laut Standard für drei Wochen nach EVLT) wurde ersatzlos abgesetzt.
Keywords: EHIT; thrombosis; endovenous; rivaroxaban